A Comparative Analysis of 2-(Thiocyanomethylthio)-Benzothiazole Degradation Using Electro-Fenton and Anodic Oxidation on a Boron-Doped Diamond Electrode. (1st March 2018) - Vázquez, Armando; Alvarado, Lucía; Lázaro, Isabel; Cruz, Roel; Nava, José Luis; Rodríguez-Torres, Israel
Abstract : 2-(Thiocyanomethylthio)-benzothiazole (TCMTB) is used as fungicide in the paper, tannery, paint, and coatings industries, and its study is important as it is considered toxic to aquatic life. In this study, a comparison of direct anodic oxidation (AO) using a boron-doped diamond electrode (BDD) and electro-Fenton (EF) processes for TCMTB degradation in acidic chloride and sulfate media using a FM01-LC reactor was performed. The results of the electrolysis processes studied in the FM01-LC reactor showed a higher degradation of TCMTB with the anodic oxidation process than with the electro-Fenton process, reaching 81% degradation for the former process versus 47% degradation for the latter process. This difference was attributed to the decrease in H2 O2 during the EF process, due to parallel oxidation of chlorides. The degradation rate and current efficiency increased as a function of volumetric flow rate, indicating that convection promotes anodic oxidation and electro-Fenton processes. The results showed that both AO and EF processes could be useful strategies for TCMTB toxicity reduction in wastewaters.